EFEKTIVITAS DAN PERILAKU PETANI DALAM MEMANFAATKAN TEKNOLOGI INFORMASI BERBASIS CYBER EXTENSION - Amin, Muh (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2014)
Information technology based on cyber extension is one of agricultural communication tools to achieve farmers welfare. Cyber extension is a technology innovation to accelerate communication of agricultural information to the user , so that information can be obtained more quickly, precisely and relevant to farmer demands.The study aimed to analyze the effectiveness and behavior of farmers in using cyber extension as a medium of communication and information in support of agricultural development. The study method was survey with 86 farmer as sample respondents. The data were analyzed descriptively and using path analysis. The results show that the effectiveness of cyber extension is influenced by the farmer characteristics, farmers interaction and farmer perception. The effectiveness of cyber extension is the most strongly influenced by farmer characteristics (coefficient rate 0.328 ), and can be seen from the availability of information technology facilities and motivation of farmers to seek required information for farming activities. On the other hand, farmer's behavior is directly influenced by farmer perception and farmer effectiveness in using cyber extension. In addition, cyber extension is strongly effective to influence farmer behaviour with a coefficient of 0.413.